The efficiency of training and hiring with intrafirm bargaining - Tripier, Fabien [Verfasser] (My University, 2011)
"This paper demonstrates that firms hire and train workers efficiently in a matching and intrafirm bargaining economy when the Hosios condition holds and returns to scale are constant. This conclusion stands in contrast to the prevailing view that training costs are a source of inefficiency in imperfect labor markets. The efficiency of the competitive economy relies on the ability of large firms to take into account the negative impact of the training rate on the wages negotiated inside the firm through intrafirm bargaining: untrained workers accept a wage reduction in compensation for potential training that is accessible only following employment. This intrafirm bargaining process solves efficiency problems associated with training costs that would otherwise lead to inefficient hiring and training decisions. This conclusion holds true for both specific and general human capital." (Autorenreferat, BIBB-Doku)
Keywords: G 1.3.1.1 Ausbildungsstellenmarkt; S 3.2 Unternehmen und Behörden; S 4.3.6 Human Capital; G 1.2.2.1 Lohn- & Tarifsysteme; S 4.3.3 Effizienz & Effektivität des Berufsbildungswesens; Ausbildungsbereitschaft; Ausbildungsverhalten; Betrieb; Personalgewinnung; Matching; Humankapital; Lohnpolitik; Tarifpolitik; Effizienz